(untitled) (Bangladesh Journal of Plant Taxonomy, 2013)
The present study focuses on the status of Reseda pentagyna Abdallah & A.G. Miller (Resedaceae). The internal transcribed spacer (ITS) region of nuclear ribosomal DNA and chloroplast trnL-F gene of the questioned species were sequenced. The Basic Local Alignment Search Tool (BLAST) search showed maximum identity with R. stenostachya. The parsimony analysis of ITS, trnL-F and combined sequences data analyses revealed grouping of Reseda species consistent with established taxonomic sections of the genus, R. pentagyna showed proximity with R. stenostachya (100% bootstrap support), nested within the clade of section Reseda. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17397 Bangladesh J. Plant Taxon. 20(2): 233-238, 2013